THE KNOWLEDGE OF TRUTH IN CLASSICAL GREEK PHILOSOPHY (Isagoge - Journal of Humanities and Social Sciences, 2022)
The study of what is truth and what is true knowledge constitute the basis for the emergence of classical philosophy, beginning this debate in the period before Socratic philosophy and culminating with the synthesis by Aristotle. From this perspective and these bases, it is possible to state that the theory of knowledge emerges with the overcoming of mythology by the pre-Socratics, insofar as the intellect, considered from sensations and senses in that first moment, becomes the reference for the explanation of reality and of the things that exist in the world. This conception will be deeply questioned after Plato and the duality he established between the sensible world and the intelligible world. It will be Aristotle, however, the first great philosopher to carry out a retrospective analysis of these theories, insofar as, on the one hand, he dismisses the senses as an essential instrument for understanding reality and the essence of things, and, on the other, the duality between the sensible world and the intelligible world as distinct realities that do not communicate objectively, Aristotelian philosophy inserts empiricism and experience as fundamental instruments for access to first principles, both realities becoming related and, therefore, fundamental to the one who launches himself to the study of philosophy and the understanding of true knowledge.
Keywords: Theory of knowledge. Truth. Pre-Socratic philosophy. Plato. Aristotle.